MUTASI PEGAWAI NEGERI SIPIL DARI PEMERINTAH KABUPATEN PELALAWAN KE PEMERINTAH PROVINSI RIAU TAHUN 2013 - Doni Munawar; Erman Muchtar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Mutation is generally a transfer of employees from one activity to another agency institutions with the aim to improve the efficient and effective operation of the organization concerned . The basic foundation of the process of mutation has been stated in Government Regulation No. 63 Year 2009 on the Authority Appointment , Removal , and Termination of Civil Servants . And the decision of the Civil Service Agency No. 70 / KEP / 2003 on the Delegation of Authority Head of Regional Office for State Personnel Board and the Agreement Establishing the Decree on Civil Service Civil Movements .Activities aimed mutation as a form of refreshment functions and duties . It is very important in improving employee performance , and spur employees to work better with the hope of getting a better position anyway . However, mutations also can be given to employees who excel and also serves as a means of giving sanction for errors or misuse that has been done by employees . There are two factors that cause mutations reasons , namely : (1) On its own desires , (2) Transfer productive tasks .This study was conducted to determine the factors that cause the number of civil servants of the Government mutation Pelalawan to Riau Provincial Government , and to determine whether the employee with a boss proximity factor is a political element in the process of mutation . Location of the study was conducted at the Regional Employment Agency and Employment Board the regency of Riau Province . The research is a qualitative study , with descriptive methods . The nature of this research is a case study .The results showed that the factors causing the number of civil servants of the Government Pelalawan mutation to the provincial government in based on their own with the main reason the family , geographic location , refreshment , and a career path .Keywords : Mutation , Civil Servants , Cause Mutatio